The Effect Of Origami Games On Fine Motor Development In Children With Stunting Diagnosis (3-5 Years) - Arfan Syahroni; Siti Nur Indah (Health Science UDINUS, 2023)
Stunting is still a problem for children in Indonesia, including in Lampung Province. Cases in Lampung Province are above the national average, namely 42.64% and the highest cases of stunting are in Central Lampung Regency with a prevalence rate of 52.68%. The purpose of this study was to analyze the effect of origami games on the fine motor development of children with a diagnosis of stunting (3-5 years) in Central Lampung Regency. The research designed was a quasi-experimental design with non-randomized control group pretest-posttest design. The research subjects were stunted children aged 3-5 years, divided into a control group and experimental group. Each group consisted of 30 respondents and was selected based on inclusion and exclusion criteria. The results of bivariate analysis of the ability to squeeze with 5 fingers between the intervention group and the control group before and after the origami game intervention p-value 0.016, ability to fold p-value 0.074, cutting ability p-value 0.018, line ablility p-value 0.034. This study it can be concluded that origami games can improve fine motor development in children with a diagnosis of stunting. It is hoped that parents can stimulate the fine motoric development of children by using the origami game method.